P73 Impact of EBUS-TBNA on Modalities For Tissue Acquisition in Patients with Lung Cancer: A Study of 407 Patients. (19th November 2012) - José, RJ; Taylor, M; Ahmed, A; Shaw, P; Brown, J; Hardavella, G; Lawrence, DR; George, PJ; Janes, SM; Navani, N
Abstract : Introduction: NICE guidance for the diagnosis and treatment of lung cancer recommends choosing "investigations that give the most information about diagnosis and staging with the least risk to the patient". [1] EBUS-TBNA is expanding as an important diagnostic modality in lung cancer and provides simultaneous information on lung cancer phenotype, genotype and nodal staging. The impact of the introduction of EBUS-TBNA on the use of diagnostic modalities for tissue acquisition in patients with lung cancer is unknown. Methods: A retrospective review of 407 consecutive patients diagnosed with lung cancer at a university teaching hospital in 2007, 2009 and 2011. Data were collected on age, gender, FEV1, performance status, diagnostic modality, and pathological subtype. Patients where only a clinical diagnosis was made (n=21) were excluded. Data were analysed using the SPSS version 17 (Chicago, IL, USA). For comparison between categorical variables, Chi-square or Fisher's exact test were used as appropriate. All reported p -values are two-tailed, and are considered statistically significant when p <0.05. Results: 386 patients were included in the analysis. The mean (SD) age (years) and FEV1 (L/min) were 69 (12) and 1.81 (0.80) for 2007, 67 (10) and 1.81 (0.79) for 2009 and 68 (12) and 2.07 (0.68) for 2011 respectively. In 2007, 2009 and 2011 57.9%, 51.4% and 62.7% were males. The results on diagnostic modalities, performance status, histological subtype and staging are listed in Table 1 . Comparing 2007 to 2011 there has been a significant reduction in standard bronchoscopy (P=0.0001), CT guided biopsy of peripheral lesions (P=0.0008) and mediastinoscopy (P=0.0382). The proportion of cases diagnosed by EBUS-TBNA significantly increased from 0% in 2007 to 21.4% in 2009 and 25.4% in 2011 (P<0.0001). There has been a significant increase in the proportion of patients going straight to surgery without pathological confirmation (p=0.002). Conclusions: The use of diagnostic modalities that provide information on diagnosis and staging in a single intervention are increasing. At our hospital, the use of EBUS-TBNA has led to a significant reduction in CT guided biopsies, standard bronchoscopies and mediastinoscopies. These changes in practise have implications for future service provision, training and commissioning. Reference: NICE Lung cancer. 2011.http://publications.nice.org.uk/lung-cancer-cg121/key-priorities-for-implementation.